Evaluation of a new retrievable post-crown system - Mohammad Mustaffa Rayyan; Ahmed Naguib Mohammed; Hanan Ahmed Naguib (Cairo : Mohammad Mustaffa Rayyan, 2008)
This study evaluated a new post-crown system as compared to another post system (flexi-post) regarding retention, microleakage, retrievability and finite element stress analysis. The results showed no significant difference between the two post systems tested regarding tensile force test. Howere when subgroups were compared only resin cement showed significant difference
Thesis (Ph.D.) - Cairo University - Faculty of Oral and dental Medicine - Department of Prothodontics
Issued also as CD
Keywords: Finite element stress analysis; Post crown; Retrievable